The role of extracellular vesicles in intercellular communication in human reproduction. Issue 3 (10th February 2023) - Gonzalez Fernandez, Javier; Moncayo Arlandi, Javier; Ochando, Ana; Simon, Carlos; Vilella, Felipe
Abstract: Embryo–maternal cross-talk has emerged as a vitally important process for embryo development and implantation, which is driven by secreted factors and extracellular vesicles (EVs). The EV cargo of bioactive molecules significantly influences target cells and primes them for critical stages of reproductive biology, including embryo development, adhesion, and implantation. Recent research has suggested that EVs and their cargo represent a powerful non-invasive tool that can be leveraged to assess embryo and maternal tissue quality during assisted reproduction treatments. Here, we review the current scientific literature regarding the intercellular cross-talk between embryos and maternal tissues from fertilization to implantation, focusing on human biology and signaling mechanisms identified in animal models.